The Thirteen Yamen and the Printing of the Yongle Nanzang in the Shunzhi Reign - Xiaodan Chen; Liang Li (Religions)
In the 15th year of the Shunzhi reign (1658), Hengming Xingmei, the abbot of Guangji Monastery in Beijing, brought a letter issued by Zhang Jiamo, the Seal-holding official of the Personnel Department 司吏院掌印, to the Jiangning Weaving Bureau, requesting the printing of the Yongle Nanzang. Before Hengming’s departure, Guangji Monastery and the former Ming eunuchs in the Qing Palace, such as Ma Hualong and Cao Huachun, maintained close contact. Cao was recommended as a keeper of imperial brushes 秉筆, by the Personnel Department, a Yamen of the Thirteen Yamen 十三衙門. Hengming probably obtained the letter through the eunuchs’ connections. The chief of the Jiangning Weaving Bureau was dispatched from the Thirteen Yamen, and the content of the letter stated that the Thirteen Yamen handled its internal affairs. The Personnel Department managed the Yongle Nanzang, while the chief of the Jiangning Weaving Bureau hosted the actual printing. The Thirteen Yamen was deeply involved in the printing of the Yongle Nanzang. Combined with the fact that Wudenghuiyuan Zuanxu 五燈會元纘續 and Miyun Yuanwu Chanshi Yulu 密雲圓悟禪師語錄 were canonized into the Yongle Nanzang by imperial decree, the Yongle Nanzang was identified as one of the Imperial Buddhist Canons in the Shunzhi Reign. Therefore, the involvement of the Thirteen Yamen in the printing of the Yongle Nanzang implicitly embodied the imperial order.